Towards an Integrated Healthcare System: Evolutionary Game Analysis on Competition and Cooperation Between Urban and Rural Medical Institutions in China - Xu, Xinglong; Liu, Jiajie; Ampon-Wireko, Sabina; Asante Antwi, Henry; Zhou, Lulin (Frontiers in Public Health, 2022)
Background The game of interest is the root cause of the non-cooperative competition between urban and rural medical and health institutions. The study investigates competition and cooperation among urban and rural medical institutions using the evolutionary game analysis. Methods With the evolutionary game model, analysis of the stable evolutionary strategies between the urban and rural medical and health facilities is carried out. A numerical simulation is performed to demonstrate the influence of various values. Results The result shows that the cooperation mechanism between urban and rural medical Institutions is relevant to the efficiency of rural medical institutions, government supervision, reward, and punishment mechanism. Conclusions Suggestions for utilizing the government's macro regulation and control capabilities, resolving conflicts of interest between urban and rural medical and health institutions is recommended. In addition, the study again advocates mobilizing the internal power of medical institutions' cooperation to promote collaboration between urban and rural medical and health institutions.